A Pilot Study of a Novel Dietary Intervention Targeting Ultra‐Processed Food Intake - Charlotte J. Hagerman; Asher E. Hong; Emma Jennings; Meghan L. Butryn (Obesity Science & Practice)
ABSTRACT Background Ultra‐processed foods (UPFs) are harmful to health but ubiquitous in the modern food environment, comprising almost 60% of the average American diet. This study assessed the feasibility, acceptability, and preliminary efficacy of a novel behavioral intervention designed to reduce UPF intake. Methods Fourteen adults participated in an 8‐week pilot intervention, which consisted of weekly group sessions, individual meal planning sessions, and financial support. Dietary intake was assessed using three Automated Self‐Administered 24‐h Dietary Recalls (ASA24) at both baseline and post‐treatment. Results The intervention was highly feasible and acceptable. Qualitative data demonstrated that participants were enthusiastic about the benefits of reducing UPF intake and found the intervention highly valuable. Participants reduced average daily calories from UPF by 48.9%, number of UPFs consumed by almost half, total daily calorie intake by 612 calories/day, sodium consumption by 37% and sugar consumption by 50%. There were no significant changes in fruit or vegetable intake. Participants lost an average of 3.5 kg (SD = 3.0 kg). Conclusion This pilot data suggests that behavioral interventions to reduce UPF intake will be well‐received and are capable of success despite the barriers of the United States food environment. Future research should prioritize behavioral interventions targeting UPF consumption alongside policy changes.